2021
DOI: 10.1182/bloodadvances.2020002408
|View full text |Cite
|
Sign up to set email alerts
|

Modeling IKZF1 lesions in B-ALL reveals distinct chemosensitivity patterns and potential therapeutic vulnerabilities

Abstract: IKAROS family zinc finger 1 (IKZF1) alterations represent a diverse group of genetic lesions that are associated with an increased risk of relapse in B-lymphoblastic leukemia (B-ALL). Due to the heterogeneity of concomitant lesions, it remains unclear how IKZF1 abnormalities directly affect cell function and therapy resistance and whether their consideration as a prognostic indicator is valuable in improving outcome. We used CRISPR/Cas9 to engineer multiple panels of isogeneic lymphoid leukemia cell lines with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…To drive B-lymphoid development, Ikaros has been reported to repress hematopoietic stem-cell-specific gene expression programs during early lineage specification [37,38]. Additionally, IKZF1 deletion in B-ALL shows a more stem cell-like signature in gene expression profiling than the wild-type IKZF1, and the expression of a stem cell program has been associated with drug resistance and poor outcomes in other types of leukemia [39][40][41]. The relapse pattern of our study suggests a role for IKZF1 in mediating drug resistance and relapse.…”
Section: Discussionmentioning
confidence: 99%
“…To drive B-lymphoid development, Ikaros has been reported to repress hematopoietic stem-cell-specific gene expression programs during early lineage specification [37,38]. Additionally, IKZF1 deletion in B-ALL shows a more stem cell-like signature in gene expression profiling than the wild-type IKZF1, and the expression of a stem cell program has been associated with drug resistance and poor outcomes in other types of leukemia [39][40][41]. The relapse pattern of our study suggests a role for IKZF1 in mediating drug resistance and relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Novel approaches to addressing IKZF1 deletions, partial or whole-gene, and their associated poor outcome in certain B-ALL subtypes, may center around overcoming the described chemotherapy resistance associated with these alterations. IKZF1 loss is associated with the stem cell gene expression signature and may thus render cells more quiescent [91]. IKZF1 loss has been associated with dexamethasone resistance in some studies, and this may be related to the degree of IKZF1 loss [91][92][93][94].…”
Section: Targeting Ikzf1-deleted B-all: Therapy Intensification and N...mentioning
confidence: 99%
“…IKZF1 loss is associated with the stem cell gene expression signature and may thus render cells more quiescent [91]. IKZF1 loss has been associated with dexamethasone resistance in some studies, and this may be related to the degree of IKZF1 loss [91][92][93][94]. In NALM6 cells, IKZF1 knockout was associated with relative resistance to daunorubicin and asparaginase, while the Tanoue cell line with IKZF1 knockout showed relative resistance to vincristine and asparaginase [91].…”
Section: Targeting Ikzf1-deleted B-all: Therapy Intensification and N...mentioning
confidence: 99%
“…Increasing evidence indicated that IKZF1 deletions mediate cellular drug resistance and relapse. For example, Rogers et.al ( 52 ) established that the IKZF1 deletion was resistant to dexamethasone, asparaginase, and daunorubicin by upregulating the JAK/STAT pathway. In addition, the IKZF1 deletion affects sensitivity to cytarabine by downregulating the SAMHD1 pathway ( 52 ); STEEGHS et.…”
Section: Clinical Significance Of Recurrent Cnv Genes In B-allmentioning
confidence: 99%
“…For example, Rogers et.al ( 52 ) established that the IKZF1 deletion was resistant to dexamethasone, asparaginase, and daunorubicin by upregulating the JAK/STAT pathway. In addition, the IKZF1 deletion affects sensitivity to cytarabine by downregulating the SAMHD1 pathway ( 52 ); STEEGHS et. al ( 14 ) suggested that the loss of IKZF1 caused prednisolone resistance by elevating intracellular ATP and glucose levels, whereas drug sensitivity was recovered by inhibition of glycolysis.…”
Section: Clinical Significance Of Recurrent Cnv Genes In B-allmentioning
confidence: 99%